Indian Urban Building Sector: CDM Potential through Engergy Efficiency in Electricity Consumption - Inderjeet Singh; Axel Michaelowa (Hamburg Institute of International Economics (HWWA), 2004)
Indian economic growth is likely to lead to a huge increase of energy use in buildings but so far, policies to address this issue are lacking. Standard building energy use concerning glazing, air conditioning and lighting in different climatic zones across India leads to energy use per m2 which is 3-4 times of the German average. We assess the potential to improve building energy efficiency and how measures in the building sector could be framed as projects under the Clean Development Mechanism. CDM case studies for large buildings in the Indian public and private sector are presented. They achieve annual greenhouse gas reductions of 500 to 10,000 ton, which may not be sufficient to overcome the CDM transaction cost barrier. Despite short payback periods, the high initial investment and lack of integrated building management makes these projects additional. Large-scale appliance dissemination programs for air-conditioners and Compact Fluorescent Lamps (CFLs) may offer interesting opportunities if the monitoring challenge can be overcome.
Keywords: Q41; Q56; Q54; 330; CDM; energy efficiency; India; buildings; Energiesparendes Bauen; Städtebaupolitik; Klimaschutz; Clean Development Mechanism; Indien